2010
DOI: 10.3151/jact.8.201
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microcracking in Concrete Subjected to Elevated Temperature at Very Early Age by Acoustic Emission

Abstract: Microcracks developed considerably in concrete subjected to elevated temperature up to around 60 o C at early ages, especially in low water-to-binder ratio (0.3) concrete. Microcracking was attributed to the stresses induced by the incompatibility in deformation between mortar and aggregate. Differences of coefficients of thermal expansion (CTE) between mortar and coarse aggregate, autogenous shrinkage of mortar and size of coarse aggregate were important factors influencing deterioration. The tensile strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Due to its size, the heat of hydration accumulated up to ~60 °C. In case of some aggregates, concrete strength development was stagnated or deteriorated because of increase in number of large pores by formation of densified outer C-S-H due to elevated temperature (Sugiyama and Masuda 1999;Gallucci et al 2013) and the difference between the volume changes in the aggregate and matrix and resultant damage accumulation around aggregates (Son and Hosoda 2010;Maruyama et al 2014b). However, in this calculation, silicate content was high and the thermal expansion of the aggregate was 10 × 10 -6 /K.…”
Section: Resultsmentioning
confidence: 74%
“…Due to its size, the heat of hydration accumulated up to ~60 °C. In case of some aggregates, concrete strength development was stagnated or deteriorated because of increase in number of large pores by formation of densified outer C-S-H due to elevated temperature (Sugiyama and Masuda 1999;Gallucci et al 2013) and the difference between the volume changes in the aggregate and matrix and resultant damage accumulation around aggregates (Son and Hosoda 2010;Maruyama et al 2014b). However, in this calculation, silicate content was high and the thermal expansion of the aggregate was 10 × 10 -6 /K.…”
Section: Resultsmentioning
confidence: 74%
“…The aggregates restrain the shrinkage of cement paste during drying or heating (Carlson 1938;Hansen and Nielsen 1965;Hobbs 1974), and the large difference in volume change, due to environmental conditions, between the aggregates and the cement paste matrix produces cracks in the cement paste that act as pores. These cracks affect the strength and Young's modulus of the concrete (Bažant et al 1982;Son and Hosoda 2010;Maruyama et al 2014b;Lin et al 2015). Therefore, the differential shrinkage is the main factor in the monotonic reduction of the Young's modulus of the concrete (Maruyama et al 2014b).…”
Section: Hardened Cement Hydrates 221 Drying and Temperature Effectsmentioning
confidence: 99%
“…The mineral compositions of OPC and HAC are calculated from the chemical composition by Bogue's equations and the main compounds of cements are listed in Table 2. Because the CTE of materials is one of the important parameters affecting microcracking in concrete 9) , two types of coarse aggregates with the same maximum particle size of 19 mm but remarkably different CTEs, namely, limestone and andesite, were used in this research. However, it should be noted here that the chemical reaction between limestone and slag mortar also affects the mechanical properties of concrete 12) .…”
Section: Experimental Programs (1) Materials and MIX Proportionsmentioning
confidence: 99%
“…2,[239][240][241][242][243][244][245][246][247][248]2014 concrete using ground granulated blast furnace slag (GGBFS) is being widely used all over the world, especially in Japan. However, Son and Hosoda found that slag concrete is also easily subjected to more severe nonstructural microcracks than OPC concrete under temperature variation at early ages 9) . It has also been recognized that slag concrete has lower resistance against carbonation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation